2014
DOI: 10.1111/jfb.12332
|View full text |Cite
|
Sign up to set email alerts
|

A method for the automated long‐term monitoring of three‐spined stickleback Gasterosteus aculeatus shoal dynamics

Abstract: This paper describes and evaluates a flexible, non-invasive tagging system for the automated identification and long-term monitoring of individual three-spined sticklebacks Gasterosteus aculeatus. The system is based on barcoded tags, which can be reliably and robustly detected and decoded to provide information on an individual's identity and location. Because large numbers of fish can be individually tagged, it can be used to monitor individual-and group-level dynamics within fish shoals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…One day prior to the start of the experiment, the standard length of all fish was measured using digital callipers (±0.1 mm) and they were non‐invasively tagged with a circular barcoded tag (5 mm diameter) attached to the middle of their three dorsal spines (Kleinhappel et al. ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One day prior to the start of the experiment, the standard length of all fish was measured using digital callipers (±0.1 mm) and they were non‐invasively tagged with a circular barcoded tag (5 mm diameter) attached to the middle of their three dorsal spines (Kleinhappel et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…; Kleinhappel et al. ,b, ). One of the main reasons that chemical information is so widely utilised within social contexts is that it is temporally flexible over short time scales and can be rapidly influenced by factors such as diet and habitat (Doane & Porter ; Bryant & Atema ; Crosland ; Schellinck et al.…”
Section: Introductionmentioning
confidence: 97%
“…A camcorder (JVC Everio GZ‐MG230) was positioned above each tank for data collection. Tagging fish for individual identification (Kleinhappel, Al‐Zoubi, et al, ) was not possible, as sticklebacks from the low pH lochs showed a reduction in dorsal and ventral spines (for example, see Figures in Giles, ; Magalhaes, D'Agostino, Hohenlohe, & MacColl, ). Therefore, each fish was placed into a transparent cylindrical plastic compartment (5 cm in diameter) with colour markings on the top identifying the specific diet treatment.…”
Section: Methodsmentioning
confidence: 99%
“…For the first two datasets, positions of the objects were provided. For our fish dataset we automatically extracted the required features: the fish were tagged using small circular discs ( [43]) attached to the dorsal spine (see Fig. 8).…”
Section: A Extraction Of Qtc Trajectoriesmentioning
confidence: 99%
“…Finally, all processing was performed off-line using an Intel Core i5-2450M laptop PC. The fish were fitted with a circular marker disc for identification and tracking [43], and the camera was mounted directly above the tank: Fig. 8 shows an example image.…”
Section: Behaviors # Of Trajectoriesmentioning
confidence: 99%